A Study of Various Factors Influencing Buying Decision Making of Health Insurance Policies - Dr. Anil Singh Parihar, Dr. Malay Ghosh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The health insurance schemes are providing a type of social security to the people. People have started buying health insurance policies and now it’s becoming popular but its reach among people are still very less. Objective: The study is conducted to determine various factors responsible for the decision making while purchasing health insurance by the people. Material and Methods: The data was collected from 240 people of Gwalior region. Various factors were extracted by applying factor analysis with the help of SPSS 18.0. Six factors were extracted which plays role in the buying decision making. Result and Discussion: The study found that there are six factors responsible for buying decision making of health insurance policies. The factors are Awareness, Company related information, Risk, Promotion, Tax benefits. Applications: The current research would help marketers to develop products which will be able to fulfil the need of society and also provide them a sense of social security. Conclusion: Public and private companies will be able to develop their products effective and according the demand of people.